Evaluating the effectiveness of RNA in‐situ hybridization for detecting lung adenocarcinoma with anaplastic lymphoma kinase rearrangement. Issue 1 (19th April 2017) - Nakajima, Naoki; Yoshizawa, Akihiko; Kondo, Kyoko; Rokutan‐Kurata, Mariyo; Hirata, Masahiro; Furuhata, Ayako; Sumiyoshi, Shinji; Sonobe, Makoto; Menju, Toshi; Momose, Masanobu; Fujimoto, Masakazu; Date, Hiroshi; et al.
Abstract : Aims: An easy and rapid assay for detecting mRNA in formalin‐fixed paraffin‐embedded samples [RNA in‐situ hybridization (ISH)] has been reported recently. The aim of this study was to investigate the diagnostic accuracy of RNA ISH in detecting lung adenocarcinoma (LA) with anaplastic lymphoma kinase (ALK) gene rearrangement. Methods and results: We tested ALK RNA ISH on 11 resected LAs for which ALK fusion was confirmed by immunohistochemistry (IHC) and/or fluorescence in‐situ hybridization (FISH). ALK mRNA expression was detected by RNA ISH in all 11 ALK ‐positive LAs, with a mean positive cell proportion of 68.4% (median, 75.3%; range, 3–98.8%), by counting 100 tumour cells at 10 different loci; RNA ISH did not detect ALK mRNA expression in the normal surrounding lung cells. Next, we explored the concordance between ALK RNA ISH and IHC/FISH tests by using tissue microarrays (TMAs) containing 294 LAs. In the TMA slides, we found five ALK ‐positive cases with IHC and/or FISH. The mean proportion of ALK RNA ISH‐positive cells in these five cases was 75.6% (median, 82%; range, 40–94%), whereas the proportion of ALK RNA ISH‐positive cells in the remaining 289 cases was 0.3% (median 0%; range, 0–15%). When the cutoff value was set at 15%, ALK RNA ISH‐positive and ALK RNA ISH‐negative cases were distinguishable with 100% sensitivity and specificity relative to the IHC/FISH tests. Conclusions: Our findings show that RNA ISH is useful for detecting ALK rearrangement with high sensitivity and specificity relative to conventional IHC/FISH tests. Thus, RNA ISH, which is an easy and rapid assay, could be an alternative method to IHC and FISH.